Catalytic cracking of vacuum gas oil on the dealuminated mordenites - Lee, KH; Lee, YW; Ha, BH (ACADEMIC PRESS INC, 1998)
Catalytic cracking of vacuum gas oil was carried out at 500 degrees C over two series of mordenites treated by either steam/HCl or HF. Secondary mesopores were formed in the mordenite by these treatments and their volumes increased with the degree of dealumination, whereas the micropore volumes decreased proportionately. The conversion of gas oil and the yield of gasoline and kerosene + diesel were correlated with the acid-amount/mesopore-volume ratio. A maximum conversion and yield were observed at a point of acid-amount/mesopore-volume ratio. This maximum point was interpreted as an optimum condition for the cracking activity between two inverse tendencies. The one is the decreasing tendency of cracking activity with reducing acid density. The other is the one increasing in activity with an increasing volume of the mesopore with silica/alumina ratio for both conversion of VGO and yields of gasoline and kerosene + diesel. On the treated mordenite of higher silica/ alumina ratio, more olefins were formed due to a low rate of hydrogen transfer reaction. Aromatics are found to be formed via cyclization of olefins which can occur inside an enlarged mesopore of dealuminated mordenite. The largest content as an alkyl-aromatic compound in the produced gasoline was toluene, which was possibly interpreted as the diffusion limitation in the formation of higher alkyl-branched aromatics. (C) 1998 Academic Press.
Keywords: FCC CATALYSTS; ZEOLITES; SELECTIVITY; DEACTIVATION; ALUMINUM; KINETICS; ALKANES; OCTANE; SILICA; STREAM